The Jurisprudential Foundation of Talabāt Company in the Mālikī School - Yousif , Nagham Ismail Mousa (Dirasat: Shari'a and Law Sciences, 2024)
Objectives: The study aims to clarify the jurisprudential adaptation of the contract between Talabat Company and restaurants according to the Maliki school. This involves individually explaining each clause's jurisprudential adaptation and subsequently assessing their combination within a single contract to determine the ruling. Methods: The study employs a descriptive method in terms of defining the concepts and the jurisprudential adaptation of the discussed issues, relying on the contract between Talabat Company and the restaurants. It utilizes the inductive method to trace scholars' opinions and applications, and the deductive method to derive legal rulings. Results: The study revealed that the contract between Talabat and restaurants combines lease (Ijārah) and agency (Jo'ālah) within a single contract, which the Maliki school deems impermissible due to their incompatibility. Conclusions: The contract between Talabat and restaurants encompasses multiple key clauses. The first involves an annual subscription fee for the restaurant, classified jurisprudentially as brokerage fees (Al Samsarah). The second clause requires restaurants to pay a commission to the company for each order made through its platform, constituting a contractual agency (Jo’ālah). The third clause pertains to the company's equipment rental to restaurants, evidently blending lease (Ijārah) and agency (Jo’ālah). Such a combination is considered impermissible according to the Maliki school.